Epidemic characteristics of diabetes in schizophrenic patients in Shanghai communities - ZHANG Yayun; WU Hemin; LU Yi; LIU Yanli; ZHANG Weibo (Shanghai yufang yixue)
ObjectiveTo explore the characteristics and associated risk factors of diabetes in patients with schizophrenia living in communities, and to provide a basis for the prevention of diabetes comorbidity in this population.MethodsA stratified cluster sampling was used to randomly select patients with schizophrenia in Shanghai who participated in the free health examination provided by the National Basic Public Health Services in 2020. Statistical methods were employed to analyze the general demographic data, clinical characteristics, and laboratory test results of the study subjects.ResultsThe study included 3 374 individuals with schizophrenia, among which the prevalence of diabetes was 17.01%. Statistically significant differences were observed in terms of age, education level, urban area type, marital status, employment status, duration of illness, blood pressure, body mass index, total cholesterol, and triglyceride levels (all P<0.05). Multivariate logistic regression analysis revealed that living in non-central urban areas (OR=1.76, 95%CI: 1.33‒2.32), disease duration of 6‒ years (OR=2.60, 95%CI: 1.07‒6.32), disease duration of 11‒ years (OR=2.72, 95%CI: 1.17‒6.35), disease duration of 16‒ years (OR=3.38, 95%CI: 1.54‒7.42), hypertension (OR=1.73, 95%CI: 1.27‒2.36), obesity (OR=1.52, 95%CI: 1.15‒2.00), and elevated triglyceride levels (OR=2.78, 95%CI: 2.22‒3.49) were risk factors for diabetes in patients with schizophrenia.ConclusionThe prevalence of diabetes in community-dwelling patients with schizophrenia is higher than that in the general population. It is recommended that appropriate health education and rehabilitation guidance be provided as part of community-based mental health services.